Digital financial literacy: Leveraging QR code technology for effective cash flow management in MSMEs - Riska Nur Rosyidiana; Mochammad Nurul; Wahyu Firmandani; Shafi Wijdan Kurniawan (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Effective management of cash flow is an essential element in sustaining and expanding Micro, Small, and Medium Enterprises (MSMEs). Inadequate financial recording and minimal digital financial literacy contribute to the challenges faced by many MSMEs in Indonesia in managing their cash flow. This program explores the capacity of QR Code technology, specifically the Quick Response Code Indonesian Standard (QRIS), to improve the management of cash flow in MSMEs. The objective of the study was to adopt QRIS as a digital payment system in order to enhance cash flow efficiency. A training and mentorship program was carried out for 30 MSMEs associated with the East Java IKM Forum. The program followed a five-stage approach, which included planning, execution, evaluation, feedback, and sustainability program. The findings demonstrate a notable enhancement in the digital financial literacy of the participants after the session. The integration of QRIS into the daily operations of MSMEs facilitated more efficient cash flow management and expanded consumer outreach. The implementation of QRIS technology shown its efficacy in enabling financial monitoring and broadening commercial prospects for MSMEs.